2022
DOI: 10.3390/ijerph192215030
|View full text |Cite
|
Sign up to set email alerts
|

A Job Demands–Resources Perspective on Kindergarten Principals’ Occupational Well-Being: The Role of Emotion Regulation

Abstract: The position of school principal is emotionally demanding. Principals’ occupational well-being (OWB) can be influenced by their emotional work characteristics, and their emotional regulation plays a critical role. Based on the job demands–resources (JD-R) model, this study investigated the relationships between kindergarten principals’ OWB and its complex antecedents. Specifically, the study examined the influences among emotional job demands and trust in colleagues on kindergarten principals’ OWB factors (job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Furthermore, several previous studies have provided evidence to support the mediating role of emotion regulation between job characteristics and work attitudes. For example, Zheng and colleagues [65] revealed that emotion regulation mediated the relationship between job demands and occupational well-being (job satisfaction and emotional exhaustion). Yin and colleagues [21] also uncovered that teachers' emotion regulation strategies mediated the relationships between emotional job demands, trust in colleagues, and teacher well-being.…”
Section: H8mentioning
confidence: 99%
“…Furthermore, several previous studies have provided evidence to support the mediating role of emotion regulation between job characteristics and work attitudes. For example, Zheng and colleagues [65] revealed that emotion regulation mediated the relationship between job demands and occupational well-being (job satisfaction and emotional exhaustion). Yin and colleagues [21] also uncovered that teachers' emotion regulation strategies mediated the relationships between emotional job demands, trust in colleagues, and teacher well-being.…”
Section: H8mentioning
confidence: 99%